Escape from camp 14 : one man's remarkable odyssey from North Korea to freedom in the West - Harden, Blaine (New York : Penguin Books, 2013)
Shin Dong-hyuk was born inside Camp 14, one of five sprawling political prisons in the mountains of North Korea. This is the gripping, terrifying story of his escape from this no-exit prison - to freedom in South Korea.
Includes bibliographic references.
Keywords: Shin, Dong-hyuk.; Political prisoners -- Korea (North) -- Biography; Concentration camps -- Korea (North); Forced labor -- Korea (North); Korea (North) -- Social conditions